Global financial orders and credit rating agencies: disruptions and adaptations - PEDRO LANGE MACHADO (Brazilian Journal of Political Economy)
ABSTRACT This paper addresses the possible disruption of the global financial order (GFO) based on the behavior of S&P Global, Moody’s and Fitch Ratings, century-old rating agencies, in face of three potentially disruptive crises: the 2008 global financial crisis, the Covid-19 pandemic and the climate breakdown. The main argument is that, historically, these agencies have adapted to the GFOs in force, mirroring their institutional and ideological parameters and thereby reflecting international tendencies. Based on an institutional historical analysis and in light of the behavior of the agencies in the crises above, it calls into question the GFO transition discussed by scholarship.